Sex-specific predictors of hearing-aid use in older persons: The age, gene/environment susceptibility - Reykjavik study. (September 2015) - Fisher, Diana E.; Li, Chuan-Ming; Hoffman, Howard J.; Chiu, May S.; Themann, Christa L.; Petersen, Hannes; Jonsson, Palmi V.; Jonsson, Helgi; Jonasson, Fridbert; Sverrisdottir, Johanna Eyrun; Launer, Lenore J.; Eiriksdottir, Gudny; et al.
Abstract Objective: We estimate the prevalence of hearing-aid use in Iceland and identify sex-specific factors associated with use. Design: Population-based cohort study. Study sample: A total of 5172 age, gene/environment susceptibility - Reykjavik study (AGES-RS) participants, aged 67 to 96 years (mean age 76.5 years), who completed air-conduction and pure-tone audiometry. Results: Hearing-aid use was reported by 23.0% of men and 15.9% of women in the cohort, although among participants with at least moderate hearing loss in the better ear (pure-tone average [PTA] of thresholds at 0.5, 1, 2, and 4 kHz ≥ 35 dB hearing level [HL]) it was 49.9% and did not differ by sex. Self-reported hearing loss was the strongest predictor of hearing-aid use in men [OR: 2.68 (95% CI: 1.77, 4.08)] and women [OR: 3.07 (95% CI: 1.94, 4.86)], followed by hearing loss severity based on audiometry. Having diabetes or osteoarthritis were significant positive predictors of use in men, whereas greater physical activity and unimpaired cognitive status were important in women. Conclusions: Hearing-aid use was comparable in Icelandic men and women with moderate or greater hearing loss. Self-recognition of hearing loss was the factor most predictive of hearing-aid use; other influential factors differed for men and women.